Health Security Begins at Reception: A Review of Frontline Triage and Biosurveillance in Primary Care and Dental Clinics - Sherwani, Fatimah Mohammed Hussain; Ghanim Yahya Mansor Okayri; Norah Awad Nafel Alharbi; Aisha Saud Ali Alenazi; Khulud Abduallah Omaysh; Sultan Rakkad Halwan Alsharari; Yahya Ahmed Ali Masrahi; Saad Dhafer Alqahtani; Nuha Abdulaziz Saad Almutairi; Shaya Mohammad Aldosari; Majidah Salem Alhejaili; Ali Mohammad Kamili (Saudi Journal of Medicine and Public Health, 2024)
Background: The initial point of contact in primary care and dental clinics represents a critical, yet vulnerable, frontier in global health security. Frontline reception and triage, often managed by health and dental assistants, serve as the first line of detection for high-consequence infectious diseases (HCIDs) and pandemic threats. Aim: This narrative review critically examines the role of clinic reception in biosurveillance, evaluates existing triage protocols, and proposes a systematic framework for empowering frontline staff as effective "first defenders." Methods: A comprehensive synthesis of literature (2010-2024) was conducted, analyzing studies on triage systems, infection prevention and control (IPC) in ambulatory settings, syndromic surveillance, and frontline healthcare worker training. Results: Significant gaps exist in inconsistent screening for travel and symptom red flags, inadequate training for non-clinical staff, poorly designed clinic flows allowing for disease transmission, and fragmented communication pathways to public health authorities. Conclusion: Health security can be substantially strengthened by standardizing "first-defender" training for reception staff, redesigning clinic layouts for rapid isolation, and integrating point-of-care diagnostics at triage. Empowering health and dental assistants is a cost-effective strategy to harden the healthcare system's entry points against biothreats.